A study of alkali polyphosphate/borate/carbonate for high temperature lubrication of silicon steel using ball-on-disc tests. (August 2021) - Wang, Long; Tieu, Anh Kiet; Ta, Huong T.T.; Xia, Chunyang; Hai, Guojuan; Wang, Yangfan; Zhu, Hongtao
Abstract: For hot metal forming at high temperatures, lubricant is required to reduce friction and wear, as well as improve the product surface quality. Inorganic compound has been regarded as a candidate to replace the traditional oil/water lubricant for the forming process. Friction and wear behaviour of three inorganic compounds, including sodium polyphosphate, sodium carbonate, sodium borate were evaluated under ball-on-disc tests at high temperature for high speed steel/silicon steel counterparts to simulate the hot rolling process. The results show that all the three compounds can reduce the friction and wear. Sodium polyphosphate is more corrosive with the oxide scale than others, which is believed to contribute to the descaling of red scale of silicon (Si) steel. Mechanisms by which the inorganic compounds improve the tribological behaviours were discussed here. Simulation results indicate that the molecules of sodium polyphosphate and sodium borate show a much higher binding energy on the iron oxide surface than that of sodium carbonate. The binding energy is mainly contributed from the ionic and the covalent interactions. The ionic part comes from the interaction between the Na + cations and the oxide surface, while the covalent part comes from the chemical bonds between Fe and oxygen of the lubricants. Both of them contribute to the adhesion of the lubricants on the steel surface and are vital to the friction and wear performance of the lubricants. Highlights: Three inorganic compounds as high temperature lubricant were evaluated using both experiments and simulation. Three compounds can reduce the friction and wear due to the formation of high temperature melt that provide easy shearing interface. Molecules of sodium polyphosphate and sodium borate show much higher binding energy on the iron oxide surface than that of sodium carbonate. This study gives guideline for design of multi-functional lubricants which reduce friction and wear, and contribute to the descaling process.